(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
This article presents comparison behavior of light-weight concretes. References of LSTSconstructionsenhancementing with light-weight concretes are expound. Keywords:light steel thin-walled structures, ceramsite concrete, polystyrene concrete, cement wood, foam concrete, cellular concrete.